PENGARUH BUDAYA ORGANISASI, LOCUS OF CONTROL, DAN STRES KERJA TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KABUPATEN OKU - Deskarfi Deskarfi; Noviansyah Noviansyah (KOLEGIAL, 2021)
This study aims to determine the Influence of Organizational Culture, Locus Of Control, and Job Stress Against Employee Performance of the Transportation Office of Oku, the population in this study were all employees of the Transportation Office of Oku who were 76 Civil Servants (PNS), the analytical method used is multiple linear regression analysis. The results of the F test calculation obtained the calculated F value of 926.756 while the F table was 2.73. This means that Simultaneously Organizational Culture, locus of control, and Job Stress significantly influence the performance of the Oku Transportation Department. Adjusted Square value of 0.974 or (97.4%) this shows the Effect of Organizational Culture, Locus Of Control, and Job Stress on Employee Performance of the Transportation Department of Oku by 97.4% while the remaining 2.6% is influenced and explained by other variables which is not included in this research model such as Work Discipline and Leadership Style.